(untitled) (International Conference on Computers in Education, 2016)
MIC-O-MAP is a technology enhanced learning environment designed for developing micro-macro thinking skills in science and engineering topics at the tertiary level. Micro-macro thinking involves the analysis of dynamic microscopic and establishing corelations to the outcomes that are measurable in the real or macroscopic world. Different students undertake multiple paths while interacting with MIC-O-MAP learning environment in an attempt to undertake the tasks of making predictions in the macro world, justifying them by establishing a micro to macro link. The focus of this study is to investigate how different students’ interactions in MIC-O-MAP leads to productive actions, i.e actions that are effective in their learning of micro-macro thinking. A grounded theory approach has been adopted for analyzing the screen capture recordings of students as they explore MIC-O-MAP, along with semi structured interviews in order to infer these actions.